2010
DOI: 10.2215/cjn.07271009
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria Is a Predictor of Chronic Renal Insufficiency in Patients without Diabetes and with Hypertension

Abstract: Background and objectives: Increased urinary albumin excretion is a known risk factor for cardiovascular events and clinical nephropathy in patients with diabetes. Whether microalbuminuria predicts long-term development of chronic renal insufficiency (CRI) in patients without diabetes and with primary hypertension remains to be documented.Design, setting, participants, & measurements: We conducted an 11.8-year follow-up of 917 patients who did not have diabetes and had hypertension and were enrolled in the Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 24 publications
0
34
0
3
Order By: Relevance
“…While final diagnosis may need a biopsy, diagnosis is usually done with measurement of urinary albumin/GFR/creatinine clearance/serum creatinine levels. 3 Microalbuminuria can be diagnosed from a 24-hour urine collection (between 30-299mg/24 hours) or, more commonly, from elevated concentrations in a spot sample (30 to 299mg/L) as done by us.…”
Section: Parameters Recordedmentioning
confidence: 99%
“…While final diagnosis may need a biopsy, diagnosis is usually done with measurement of urinary albumin/GFR/creatinine clearance/serum creatinine levels. 3 Microalbuminuria can be diagnosed from a 24-hour urine collection (between 30-299mg/24 hours) or, more commonly, from elevated concentrations in a spot sample (30 to 299mg/L) as done by us.…”
Section: Parameters Recordedmentioning
confidence: 99%
“…Concordantly, it has been demonstrated that CV risk progressively increases in parallel with the renal function decline [17]. Early signs of renal damage, such as microalbuminuria, mild decrease in estimated glomerular filtration rate (eGFR), and increased renal vascular impedance, are relatively common conditions in patients with primary hypertension [18].…”
Section: Arterial Stiffness Cardiovasculatr Risk and Chronic Renal Dmentioning
confidence: 99%
“…According with this, microalbuminuria, as well as a mild reduction in eGFR, have been indicated to be associated with a higher risk of CV disease as well as increased CV morbidity and mortality [17,18]. Further, increased renal vascular impedance has been demonstrated to correlate with early signs of CV and renal damage [19] and to predict the progression to end-stage renal disease in primary renal disease [20].…”
Section: Arterial Stiffness Cardiovasculatr Risk and Chronic Renal Dmentioning
confidence: 99%
“…DN is also the most common leading cause of end-stage renal disease (ESRD) worldwide [1-3]. Conventionally, microalbuminuria (MA; 30–300 mg/24 h) is considered a biomarker and a risk for DN and progressive renal dysfunction [4-10]. However, several studies have questioned the sensitivity and the specificity of MA for renal dysfunction [11].…”
Section: Introductionmentioning
confidence: 99%